Downregulation of HMGA2 by Small Interfering RNA Affects the Survival, Migration, and Apoptosis of Prostate Cancer Cell Line - Shima Khajouee; Elham Baghbani; Ali Mohammadi; Behzad Mansoori; Dariush Shanehbandi; Khalil Hajiasgharzadeh; Behzad Baradaran (Tabriz University of Medical Sciences, 2022)
Purpose: To investigate the downregulation of high mobility group AT-hook 2 (HMGA2)expression by small interfering RNAs (siRNAs) in PC3 prostate cancer cell line. HMGA2belongs to the non-histone chromatin-binding protein family that serves as a crucial regulator ofgene transcription. The overexpression of this gene is positively correlated with various prostatecancer (PC)-related properties. Thus, HMGA2 is an emerging target in PC treatment. This studyaimed to examine the impact of siRNAs targeting HMGA2 on the viability, migration, andapoptosis processes of the PC3 PC cell line.Methods: siRNA transfection was conducted with a liposome-mediated approach. The mRNAand protein expression levels for HMGA2 are evaluated by real-time polymerase chain reaction(qRT-PCR) and western blot analysis. The cytotoxic properties of HMGA2-siRNA were measuredby MTT assay on PC3 cells. The migration of PC3 cells was measured by implementing awound-healing assay. Apoptosis measurement was also quantified by TUNEL assay.Results: Transfection with siRNA significantly decreased both mRNA and protein levels of theHMGA2 gene in a dose-dependent manner after 48 hours. Also, we demonstrated that theknockdown of HMGA2 led to a reduction in cell viability, migration ability, and enhancedapoptosis of PC3 cells in vitro.Conclusion: Our findings recommend that the specific siRNA of HMGA2 may efficiently beable to decrease PC progression. Therefore, it may be a promising adjuvant treatment in PC.